Pan-Genome Analysis of Vibrio cholerae and Vibrio metschnikovii Strains Isolated From Migratory Birds at Dali Nouer Lake in Chifeng, China - Zheng, Lin; Zhu, Ling-Wei; Jing, Jie; Guan, Jia-yao; Lu, Ge-Jin; Xie, Lin-Hong; Ji, Xue; Chu, Dong; Sun, Yang; Chen, Ping; Guo, Xue-Jun (Frontiers in Veterinary Science, 2021)
As a new Vibrio carrier concerned, migratory birds with characteristics of wide spread. We isolated V. cholerae and V. metschnihovii from migratory bird epidemic materials from 2017 to 2108 and isolated V. metschnihovii from migratory bird feces in 2019, Inner Mongolia autonomous region, China. To investigate the evolution of these two Vibrio species, we genome-sequenced forty V. cholerae strains and thirty-four V. metschnihovii strains, and compared with known sequenced strains obtained from GenBank database. The pan genome of all V. cholerae and V. metschnihovii were open, and the strains showed individual differences. The numbers of V. cholerae and V. metschnihovii core gene were 2130 and 1352, and the number of dispensable genes of them were 16180 and 9178 respectively. All V. cholerae strains isolated from migratory bird with T6SS and hlyA, were non-O1/O139 serotype without CTX. Those strains also without TCP fimbriae, extracellular matrix protein RbmA, and cannot utilize TMAO. They couldn’t evolve to pandemic strains. In this study, V. metschnihovii strains with the complete T6SS was isolated for the first time. Our data corroborated and provided molecular explanations for phenotypic studies of migratory bird V. cholerae and V. metschnihovii.